Pergeseran Kekuasaan Tipologi Ketiga; Fenomena Kekuasaan Ke Arah Constitusional Heavy - Puguh Windrawan (Jurnal Konstitusi, 2016)
The Constitutional Court plays a central role in the democratic system governance. With a solid perspective of balancing  state  power,  the  court  has  been set up to interpret and review of conformity of every act and regulation. In Indonesia, a constitutional court presence has an important meaning amid power shifting processes. As the supremacy to some extent moving away from the executive authority, the constitutional court appears as the most prominence body instead of legislative board. In accordance with its duties and functions, the institution is able to give juridical interpretations to examine every regulation against The Constitution of The Republic of Indonesia 1945.